Efforts to Improve the Learning Process of Students Using the Learning Start with a Question Learning Method in Science Subjects in Class IV SD Islam At Taubah - Septi Fitri Meilana; Anissha Anissha (Universitas Muhammadiyah Enrekang, 2022)
The success of the learning process is closely related to the teacher's role in educating students at school so that teachers need to innovate and streamline the learning process so that the quality of learning increases. The aim of the study was to find out the learning process of students using the learning start with a question learning method in science subjects in class IV SD Islam At Taubah. The research used by researchers is classroom action research. Class action research was conducted at At Taubah Islamic Elementary School for science subjects about energy in grade IV. The research was conducted in May 2022. The subjects in this research were fourth grade students at At Taubah Islamic Elementary School with a total of 29 students, of which 13 were boys and 16 were girls. Science learning using the learning start with a question method can improve the student learning process, especially on the Kayanya Negeriku theme. This is indicated by the average in cycle I with an average value of 73.61, in cycle II with an average student value of 77.67, and in cycle III the average student value is 82.07. If the percentage of students' natural science scores sequentially met the KKM, namely cycle I was 44.83%, cycle II was 67.24%, and cycle III was 93.10%. With an increase in the learning process from cycle I to cycle II, namely 4.06, while the increase from cycle II to cycle III, namely 3.36. Science learning using the learning start with a question method is proven to be able to attract students' attention and is more active, effective, and, as well as increasing motivation and skills in solving problems and increasing the quality of learning so that it has an impact on student learning outcomes.